Strategies of Supply Chain Management in the Global Economy - RajaShekhar, B. (Indian Journal of Marketing, 2004)
Businesses the worlds over are struggling to sustain competitiveness in a globalized economy. They are at present in the midst of a revolutionary transformation: that of competition shifting from industrial age to the information age. Information age competition has initiated some unique challenges, which the businesses have to cope up with. Business environment’s uncertainty has become a way of life. Accordingly, companies are finding it even more difficult to predict changes in their competitive environment. Customers are becoming competitors; competitors are becoming partners and unconventional competition is emerging. Businesses, however, must go on despite dramatic new business environments, that are at present not well understood.